(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
This article examines the role of information and communication technologies in the modern educational process. The use of information technology makes it possible to individualize the educational process by providing opportunities for students to both study the subject in depth and practice elementary skills and abilities. In this article, the author presents to your attention the importance and significance of the use of computer technology in physics lessons.